Phospholipase A(2) Inhibitors from Snake Blood (sbPLIs) - Fortes-Dias, Consuelo L.; Campos, Patricia Cota; Fernandes, Carlos Alexandre H. [UNESP]; Fontes, Marcos Roberto M. [UNESP]; Inagaki, H.; Vogel, C. W.; Mukherjee, A. K.; Rahmy, T. R.; Gopalakrishnakone, P. (Springer, 2017)
Several snake species have been naturally provided with protein inhibitors with the primary aim of self-protection against the eventual presence of venom toxins in their circulating blood. Phospholipase A(2) inhibitors are among the most studied molecules in that group. Such molecules have been identified in venomous and nonvenomous snake species and are generally known as sbPLIs (which stand for snake blood phospholipase A(2) inhibitors). Based on the presence of known domains of mammalian proteins, sbPLIs may belong to any of three structural classes (alpha, beta, or gamma). All the domains are involved in protein-protein interactions. The sbaPLIs present a characteristic C-type lectin-like domain (CTLD) highly similar to the carbohydrate recognition domain (CRD) of Ca2+-dependent lectins, which includes mannose-binding and lung surfactants A and D (SP-A and SP-D) proteins. Beta-type inhibitors (sb beta PLIs) are characterized by the presence of nine tandem leucine-rich repeats (LRRs), whereas sb.PLIs share the characteristic three-finger motifs of the Ly-6 family, CD59 and the urokinase-type plasminogen activator (u-PAR). Despite of no crystallographic data of sbPLIs, several computational and biophysical techniques have been applied, in an effort to provide structural data for structure-function relationships between these inhibitors and svPLAs. This chapter will be devoted to a brief but not extensive review of general aspects, quaternary structures, molecular mechanisms, and applications of sbPLIs.
Keywords: Phospholipase A(2); PLA(2); PLA(2) inhibitor; sbPLI; Snake